Protein-protein interactions: modeling the hepatitis C virus ion channel p7. - Patargias, G; Zitzmann, N; Dwek, R; Fischer, W (American Chemical Society, 2005)
The p7 protein is a small ion-channel-forming membrane polypeptide encoded by the hepatitis C virus which consists of two transmembrane alpha-helices, TM1 and TM2, and can be blocked by long-alkyl-chain iminosugar derivatives. The length of TM1 and TM2 was estimated by employing different secondary structure prediction algorithms and is proposed to span from Ala-10 to Leu-32 for TM1 and from Trp-36 to Pro-58 for TM2. A configurational search protocol based on simulated annealing combined with short restrained molecular dynamics simulations is used in addition to protein-protein docking to investigate the packing of TM1/TM2. Full p7 oligomeric bundles were generated, and in the most plausible models serines and threonines are facing the hydrophilic pore. In these models, His-17 would be a pore-facing residue, suggesting that p7 may be sensitive to pH in respect to its function.